Protein repeats: structures, functions, and evolution. - Andrade, M; Perez-Iratxeta, C; Ponting, C (2001)
Internal repetition within proteins has been a successful strategem on multiple separate occasions throughout evolution. Such protein repeats possess regular secondary structures and form multirepeat assemblies in three dimensions of diverse sizes and functions. In general, however, internal repetition affords a protein enhanced evolutionary prospects due to an enlargement of its available binding surface area. Constraints on sequence conservation appear to be relatively lax, due to binding functions ensuing from multiple, rather than, single repeats. Considerable sequence divergence as well as the short lengths of sequence repeats mean that repeat detection can be a particularly arduous task. We also consider the conundrum of how multiple repeats, which show strong structural and functional interdependencies, ever evolved from a single repeat ancestor. In this review, we illustrate each of these points by referring to six prolific repeat types (repeats in beta-propellers and beta-trefoils and tetratricopeptide, ankyrin, armadillo/HEAT, and leucine-rich repeats) and in other less-prolific but nonetheless interesting repeats.